If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(x+2)+9=3x+3
We move all terms to the left:
3(x+2)+9-(3x+3)=0
We multiply parentheses
3x-(3x+3)+6+9=0
We get rid of parentheses
3x-3x-3+6+9=0
We add all the numbers together, and all the variables
12!=0
There is no solution for this equation
| 0.2x+3.1=0.7x-0.4 | | -25=-2x+7;16 | | |-4c+15|=35 | | |8x-1|=4 | | 5x+40+2x-60=180° | | 3x-5=6x+35 | | 4(u+2)-7u=-13 | | 3x-+7-11x=31 | | 1(-5y+1)=-14 | | 5(2x+7=-23+18 | | -4=2.5x+10 | | 25y=y-11 | | −7z4=14 | | A=2.5x+10 | | 3x-27=-4x+15 | | 5x+40+2x-60=180 | | 14+3(5t-12)=1-(20t+1) | | 6+6y-15=39 | | (3x5^2/15)-(5-2^2)=0 | | 72=-9xX2 | | 14=c2+ 12 | | (2/3)w-1/2=1/4 | | y+3=2y+4 | | -2j+16.52=2.52 | | 9+b/4=7 | | -11(x+26)-27(x+26)=15x-15 | | 3x+-8=15 | | 6=j2− –4 | | 2x-8x-13=6x+5-13 | | 7.5x+30=x | | j/4+27=35 | | -5+2x/5=5 |